Chained for life [videorecording (DVD)] - Schimberg, Aaron; Schimberg, Aaron; Weixler, Jess; Pearson, Adam; Plunkett, Stephen, 1981- (Kino Lorber, 2020)
Follows an actress who plays a blind woman and an actor who was cast because of his facial tumors during the making of an art-horror film.